Pine Trees, Trolls and Golden Windows: A Tale of Two Grandfathers - von Maltzahn, Maia (The International Journal of Whole Person Care, 2025)
In this brief personal essay, the author explores her relationship with her two grandfathers, and traces their influence in her path to Geriatric Medicine. She reflects on lessons and stories imparted by her grandfathers, and the wisdom that can be gained from listening to the perspectives of others.